Tailoring Adaptive Social Safety Nets to Latin America and the Caribbean - Williams, Asha; Martinez, Ursula (World Bank, Washington, DC, 2020)
Social safety nets (SSNs) are increasingly relevant to helping households prepare, cope, and adapt to shocks in a climate of increased frequency and severity of disasters. Disasters can impact the income, consumption, and human capital of households. While disasters caused by natural hazards can impact anyone, the poor often bear the brunt of shock impacts, while vulnerable and other disadvantaged populations fall into poverty. When poor people are affected, the share of their wealth lost is two to three times that of the non-poor, largely because of the nature and vulnerability of their assets and livelihoods. The poor also often employ negative coping strategies following disasters, with long-lasting effects on human capital accumulation and income. Where SSNs have good coverage, adequacy, and incidence, they help ensure that the households most likely to be severely impacted by these events are able to smooth their consumption, build human capital, improve their assets and diversify livelihoods - all of which are increasingly critical to better preparedness for shocks and improved ability to cope with, and recover from, their impacts. An increasing number of countries have used their SSNs, primarily cash transfers and in-kind transfers, to respond to household needs following different shocks including disasters caused by weather and geological events, economic crisis and most recently, the economic crisis due to the COVID-19 health pandemic. Latin America and the Caribbean (LAC) exhibits larger coverage and expenditures on SSNs compared to most regions, particularly for cash transfer programs. SSNs in LAC also demonstrate comparatively well-established SSN delivery systems. Given this, there is unlocked potential in LAC to effectively respond to disasters by systematically using SSNs when appropriate. This note presents key lessons and design considerations for LAC countries to better usetheir SSNs to help individuals and households prepare, cope and adapt to the shocks they face. While this note focuses on disasters caused by natural hazards, the framework and lessons presented here are applicable to other types of emergencies and shocks.